Puerarin Increases Survival and Protects Against Organ Injury by Suppressing NF-κB/JNK Signaling in Experimental Sepsis - Wang, Lei; Liang, Qiao; Lin, Anqi; Chen, Xiufang; Wu, Yongzhen; Zhang, Bin; Zhang, Yu; Min, Haiyan; Wen, Yanting; Song, Shiyu; Gao, Qian (Frontiers in Pharmacology, 2020)
Puerarin, an isoflavonoid rich in Radix Puerariae, has been reported to be a broadly effective regulator in various biological processes and clinic conditions. However, the role of puerarin in sepsis-induced mortality with multiple-organ injury remains unknown. Herein, we showed that puerarin potently attenuated organ injury and increased survival rate in both lipopolysaccharides (LPS) and cecal ligation and puncture (CLP) induced mouse sepsis models. It greatly suppressed systemic inflammation, determined by the serum levels of proinflammatory factors TNF-α, IL-6, IL-1β, IL-10, as well as monocyte chemotactic protein-1 (MCP-1) and C-reactive protein (CRP). Flow cytometry analysis indicated that puerarin settled overall inflammation mainly by normalizing expanded macrophages with limited effects on dendritic cells and CD4+T cells in the circulation of sepsis mice. In the liver, puerarin inhibited the transcription of inflammatory factor TNF-α, IL-6, and IL-1β and protected hepatocyte apoptosis in sepsis mouse models. In vitro, puerarin inhibited LPS-induced inflammation in LO2 hepatocytes, prevented TNF-α-mediated cell apoptosis and promoted an M2 phenotype revealed by M2 marker IL-10 and Arginase-1 (Arg-1) in LPS challenged Raw 264.7 macrophages, through the inhibition of TLR4/NF-κB/JNK pathway. In conclusion, puerarin reduced systemic inflammation and protected organ injury in sepsis mice, thus, it might provide a new modality for a better treatment of sepsis.